Headhunter - Davidson, Jay; Schaeffer, Francis ([USA] : William Productions)
In the heart of Africa... some call it an ancient curse, some call it absolute evil. Terror slowly grips the city's population as a series of gruesome murders take place. They are so violent and ghastly in their execution that it's difficult for veteran homicide cop Pete Giulani and Katherine'Kat' Hall to face the incredible altermath. Adding to the mystery, they find the words'I Thirst' scrawled in blood on the victim's wall. At one of the crime scenes a stately black Shaman introduces himself to the detectives and calmly explains that the headhunter, a dangerous being of immense power is performing the macabre deeds. he informs them of the headhunter's ability to change his shape and impersonate other humans. If he is allowed to claim three more victims, his poers will become limitless. Kat almost become the next victim when she is summoned by the headhunter, who impersonates Pete's voice! She arrives at the appointed meeting spot and sees the headhunter's true and terrifying form. she barely survives her encounter with it. Now ture believers, Pet and Kat rush to the Shaman for answers but are stunned to find he is the latest victim.
Executive producer, Gregory Small ; editor, Robert Simpson
Cast: Kay Lenz, Wayne Crawford, Steve Kanaly, John Fatooh
Keywords: Ghosts in motion pictures; Violence in motion pictures